Med-nursing motivations and emerging issues - Manalo, Cherry A. (2006)
The unusual outflow of doctors has caught the medical sector by surprise because their colleagues are leaving to work abroad not as doctors but as nurses. Likewise, it has created issues which when left unattended will leave an indelible mark in the medical profession and medical care provision in the country. Aimed at unleashing the motivations of doctors for taking up nursing, how these motivations affected their positive and negative attitude on the phenomenon, and emerging issues and implications in relations to the advancement of industrial relations theories and provision of medical care to the Filipinos, this study covered 77 doctors taking the Nursing Program between August 2003 and September 2005 in selected Nursing School in Metro Manila. The researcher used both historical and survey methods in gathering data where the respondents were selected through a modified multi-stage sampling. Statistical tests used in analyzing data were regression, T-Test and ANOVA with the help of Microsoft Excel and Statistical Package for Social Sciences (SPSS) programs. Findings of the study revealed that the major factor motivating doctors to take up nursing was economic, with emphasis on the future of their children. Top five reasons point to the strong desire of doctors to migrate to the country. Hypotheses testing showed a positive relationship between both socio-demographic variables and socio-economic and political reasons, and overall positive attitude of doctors toward taking up nursing. Emerging issues include feminization of the med-nursing phenomenon, the tendency of doctors to shift into the nursing profession when socio-economic and political conditions in the country are not improving, and the impending loss of mission critical skills and occupations. Such issues indicate a changing paradigm of doctors that impact on the industrial relations system in the medical sector, specifically on its future environmenta; conditions, changes in the supply characteristics of Filipino doctors, changes in employment relationships,and management of mobility of healthcare professionals. It is recommended therefore that the stakeholders should take strategic actions in order to contain the situation and address the issues confronting the medical sector and the provision of health care in the country. Among the proposed actions are : establishing an official on-line data base for health human resources, including values education in the medical curriculum, crafting of a law that will regulate the movement of critical skills and professions; facilitating and strengthening the health tourism program of the government, and increasing the national health budget for improvement of facilities of government hospitals and enhancement of skills of healthcare professionals.